Stabilization of silver nanoparticles in a transparent polymethacrylate matrix while maintaining the capabilities of a colorimetric hydrogen peroxide sensor - Saranchina N. V. Nadezhda Vasilievna; Bazhenova O. A. Olga Aleksandrovna; Bragina S. K. Sofjya Konstantinovna; Gavrilenko N. A. Natalia Airatovna; Gavrilenko M. A. Mikhail Alekseevich; Volgina T. N. Tatiana Nikolaevna (2024, 2024)
Title screen